CEGAH STUNTING DARI RUMAH: LITERASI GIZI BAGI IBU BALITA DI POSYANDU PALEM KECAMATAN GEDEBAGE - Januarsyah, Gilang; Handayani, Vincentia Tri (Midang, 2025)
Stunting remains a major nutritional problem affecting children’s growth and development, particularly in urban areas with high levels of parental busyness such as Gedebage District, Bandung City. Low nutritional literacy among mothers of toddlers is one of the main factors leading to unbalanced feeding practices and limited attention to child growth monitoring. This community service activity aimed to improve maternal nutrition literacy through an educational counseling program at Posyandu Palem. The program was carried out in three stages: preparation, implementation, and simple evaluation. The face-to-face counseling session lasted for two hours and involved twenty mothers of toddlers and eight Posyandu cadres. The materials were delivered interactively through discussions, visual presentations, and leaflets to accommodate participants with various educational backgrounds. The results showed an increase in mothers’ knowledge and awareness of balanced nutrition, particularly regarding the relationship between stunting, brain development, and children’s immunity. Some participants began to show positive behavioral changes in choosing food ingredients and preparing family meals. However, several challenges remained, including limited time, children’s food preferences, and lack of family support. Overall, this activity demonstrated that participatory educational counseling is an effective approach to strengthening maternal nutrition literacy and serves as a strategic step in preventing stunting at the household level.